2013
DOI: 10.1007/s10096-013-1999-1
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the serum biomarker profiles of visceral leishmaniasis during treatment

Abstract: Until recently, chemotherapy for visceral leishmaniasis (VL; also known as kala-azar) was severely limited by factors such as high cost, route of administration, generation of side effects and potential for resistance. Although largely effective chemotherapies have become available with the introduction of new drugs and multi-drug regimens for VL, these could be further improved by the identification of biomarkers that are altered during effective treatment. The identification of such biomarkers in the circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
4
24
0
1
Order By: Relevance
“…IFN-␥ levels were found to be significantly elevated in patients with active VL, which was confirmed in a wide range of countries: India (74,75), Bangladesh (70), Brazil (70,72,73,77), Ethiopia (67, 68), Sicily (66), and Iran (65). During and after successful treatment, IFN-␥ levels were found to drop significantly but remained elevated compared to levels in healthy controls (66,70,73,75,78). In contrast, Cenini et al (84) showed that IFN-␥ levels returned to healthy-control levels at the end of treatment.…”
Section: Identified Biomarkersmentioning
confidence: 79%
See 4 more Smart Citations
“…IFN-␥ levels were found to be significantly elevated in patients with active VL, which was confirmed in a wide range of countries: India (74,75), Bangladesh (70), Brazil (70,72,73,77), Ethiopia (67, 68), Sicily (66), and Iran (65). During and after successful treatment, IFN-␥ levels were found to drop significantly but remained elevated compared to levels in healthy controls (66,70,73,75,78). In contrast, Cenini et al (84) showed that IFN-␥ levels returned to healthy-control levels at the end of treatment.…”
Section: Identified Biomarkersmentioning
confidence: 79%
“…The increase of IL-10 concentrations in VL patients was later confirmed in a range of countries, including, among others, India, Brazil, and Ethiopia (65-77). IL-10 levels were found to drop significantly after successful treatment (66,70,73,78) to near-control levels 5 to 7 days posttreatment (74). Ansari et al found no difference in pretreatment IL-10 levels between responsive and unresponsive patients (74).…”
Section: Identified Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations